Syndromic surveillance using regional emergency medicine internet()()()()() - Foldy, Seth (Ann Emerg Med, 2004)
STUDY OBJECTIVE: We demonstrate the feasibility and utility of emergency department (ED) syndromic surveillance using a regional emergency medicine Internet application to minimize impact on ED and public health staffing. METHODS: Regional (multi-ED) surveillance was established for 2 periods, one characterized by a high-profile national sports event and the other during an international disease outbreak. Counts of patient visits meeting syndrome criteria and total patient visits were reported daily on the secure regional emergency medicine Internet site and downloaded by public health staff. Trends were analyzed and displayed on the secure Web site. ED participants were surveyed about the acceptability and time cost of the project. RESULTS: In the first (“All Star Game”) project, 8 departments reported daily counts for 4 weeks, covering more than 26,000 patient visits. In the second (“severe acute respiratory syndrome” [SARS]) project, an average of 11 departments in the same region reported daily data on febrile respiratory illnesses, travel, and contacts for 10 weeks. Experience with the first project allowed for rapid implementation of the second project during a 3-day period. In both instances, the surveillance efforts were undertaken without the need for extraordinary ED or public health staffing requirements. CONCLUSION: A regional emergency medicine Internet approach permitted rapid implementation of multisite syndromic surveillance without additional staff. Some problems were identified with the first project, related to clinician checklist completion and manual data tabulation and entry. The SARS project addressed these by simplifying data collection and restricting it to triage.